Measurement of the $$ {\textrm{B}}_{\textrm{s}}^0\to \textrm{J}/{\uppsi \textrm{K}}_{\textrm{S}}^0 $$ effective lifetime from proton-proton collisions at $$ \sqrt{s} $$ = 13 TeV - Null, Null; Hayrapetyan, A.; Tumasyan, A.; Adam, W.; Andrejkovic, J. W.; Bergauer, T.; Chatterjee, S.; Damanakis, K.; Dragicevic, M.; Hussain, P. S.; Jeitler, M.; Krammer, N.; et al. (Springer Science and Business Media LLC, 2024)
Abstract The effective lifetime of the $$ {\textrm{B}}_{\textrm{s}}^0 $$ B s 0 meson in the decay $$ {\textrm{B}}_{\textrm{s}}^0\to \textrm{J}/{\uppsi \textrm{K}}_{\textrm{S}}^0 $$ B s 0 → J / ψK S 0 is measured using data collected during 2016–2018 with the CMS detector in $$ \sqrt{s} $$ s = 13 TeV proton-proton collisions at the LHC, corresponding to an integrated luminosity of 140 fb −1. The effective lifetime is determined by performing a two-dimensional unbinned maximum likelihood fit to the $$ {\textrm{B}}_{\textrm{s}}^0 $$ B s 0 meson invariant mass and proper decay time distributions. The resulting value of 1.59 ± 0.07(stat) ± 0.03(syst) ps is the most precise measurement to date and is in good agreement with the expected value.
Keywords: Physics; ddc:530; info:eu-repo/classification/ddc/530; B Physics; Hadron-Hadron Scattering; Lifetime